The relationship between VAICTM, company performance and market value of companies on the Johannesburg Securities Exchange - Dullabh, Hitesh (Department of Finance and Tax, 2023)
Purpose - The purpose of this paper was to examine the impact of Intellectual Capital (IC), using the VAICTM approach, against certain company performance indicators as well as market value on listed companies in South Africa. Design/Methodology/Approach - The study used secondary data of 50 listed companies from the Johannesburg Securities Exchange (JSE) over a period of five years (2016-2020), obtained from the IRESS Expert Database, as a basis for its analysis of the relationship between VAICTM (IC), company performance and market value. IC and its components are calculated using Pulic's (2000) VAICTM approach. Company performance is measured by Return on Assets (ROA) and Asset Turnover (ATO). Market value is measured by the Tobin's Q calculated as market to book ratio (TQ). The two-way Fixed Effects regression model is applied to statistically test the relationship between IC and company performance indicators , as well as the relationship between IC and market value. Findings - The results indicate that VAICTM and capital employed efficiency (CEE), are positively and significantly associated with market value of listed companies in South Africa. The relationship between the remaining components of VAICTM, Human Capital Efficiency (HCE) and Structural Capital Efficiency (SCE), and company performance and market value was not found to be statistically significant. Practical Implications - Within the South African context, physical and financial capital (represented by CEE) plays a dominant role in how market participants value the company, whilst HCE and SCE seem to have less of an influence on the market's perception of value. The recognition value by market participant, albeit confined to just one of the components of VAICTM, may be indicative of the market pre-empting such value in company performance going forward. These findings provide insight into the role that investment in IC can play in supporting company performance and market value of the company. v Originality/Value - This study provides a more recent analysis of the original work performed by Firer & Williams (2003) and Firer & Stainbank (2003). It also provides insight into progression and recognition of IC in the South African Market. Finally, this study contributes to the still limited body of academic literature on the relationship between the company's IC, its performance and its market value. The significance of this contribution is its focus on companies in an emerging market and the focus on South African companies in particular, given the dearth of such studies with this particular focus.